Valorisation of urban waste to access low-cost heterogeneous palladium catalysts for cross-coupling reactions in biomass-derived γ-valerolactone. Issue 16 (27th July 2021) - Valentini, Federica; Ferlin, Francesco; Lilli, Simone; Marrocchi, Assunta; Ping, Liu; Gu, Yanlong; Vaccaro, Luigi
Abstract : Herein we report a simple protocol for the valorisation of a common urban biowaste. Abstract : Herein we report a simple protocol for the valorisation of a common urban biowaste. The lignocellulosic biomass obtained after the pre-treatment of pine needle urban waste is efficiently transformed into a low-cost support (PiNe) for the immobilization of Pd nanoparticles. The final Pd/PiNe heterogeneous catalyst features a small particle size (4.5 nm) and a metal loading (9.9 wt%) comparable with most commercially available and generally used counterparts. In this contribution, we tested the catalytic efficiency of the Pd/PiNe system in two representative cross-couplings, Heck and Hiyama reactions, and compared the results obtained with commercial Pd/C catalyst. The good reactivity in the biomass-derived solvent (GVL) confirms that the Pd/PiNe heterogeneous catalyst is a valid system that can be integrated into a waste valorization chain within a circular economy approach. In addition, the efficiency of the catalyst has also been extended to perform the challenging consecutive Hiyama–Heck reaction to afford differently substituted ( E )-1, 2-diarylethenes.